Constructions of time and history in the pre-Columbian Andes - Swenson, Edward; Roddick, Andrew P. (University Press of Colorado, 2018)
"Explores archaeological approaches to temporalities, social memory, and constructions of history in the pre-Columbian Andes. Examining a range of Indigenous temporal experiences and ideologies, including astronomical, cyclical, generational, eschatological, and mythical time to challenge outmoded theories while building on an emic perspective to gain greater understanding"--Provided by publisher